PENERAPAN METODE GEOGRAPHICALLY WEIGHTED REGRESSION (GWR) PADA KASUS PENYAKIT COVID-19 DI PROVINSI BALI - SUCIPTAWATI, NI LUH PUTU; SUGIANTARI, NI MADE SRI; SUSILAWATI, MADE (E-Jurnal Matematika, 2023)
COVID-19 has spread widely to all parts of the world, including Indonesia. Bali is included in the top ten with the highest number of COVID-19 cases in Indonesia. The spread of COVID-19 is thought to be influenced by various factors in each location that cause spatial heterogeneity. The method that can be used to analyze if there is spatial heterogeneity is Geographically Weighted Regression (GWR). This study aims to model the factors that influence the number of COVID-19 cases in Bali. The results showed that the GWR model with the adaptive kernel bisquare weighting function was more suitable to be used to model the number of COVID-19 cases in Bali because it had the largest  value of 96.36%. The factors that influence the number of COVID-19 cases in Bali are population density and the population aged 20-44 years old.